Laboratory evaluation of the susceptibility of adult Africa Invader Fly, Bactrocera invadens (Diptera: Tephritidae) To NuLure-based bait of some selected insecticides commonly used by mango farmers in Ghana - Abdullahi, G.; Obeng-Ofori, D.; Afreh-Nuamah, K.; Billah, M.K. (Global Journal of Science Frontier Research, 2011)
True fruit flies are one of the world’s worst pests of fruit and fruiting vegetables, causing millions of dollars worth of damage each year. While Africa has a number of native fruit flies of its own, some exotic species present in some continents has in recent years raised some serious biosecurity concerns among local experts. Bactrocera invadens is one of the exotic fruit flies that recently invaded Africa. Evidence of competitive displacement of indigent fruit flies in some mango agro ecosystem by this species has been recently documented. Effective control of these fruit flies can best be achieved through an IPM based control programme which will involve the use of bait in traps or spot treatments. However, no fruit flies bait is currently registered and is available on Ghanaian market for use in the management of this species by the farmers. The use of some readily available insecticidal products namely Cydim Super, Pyrinex 50 EC, Diazol 50 EW and Deltapaz as killing agents in the commercially available food bait Nulure was evaluated in the laboratory to ascertain their efficacy. The result show that Pyrinex and Diazol based bait were the most effective bait that can be used for the management of fruit flies in Ghana.
Keywords: Bactrocera invadens; bait; NuLure; Fruit flies